PELAYANAN PUBLIK MELALUI ELECTRONIC GOVERNMENT: UPAYA MEMINIMALISIR PRAKTEK MALADMINISTRASI DALAM MENINGKATAN PUBLIC SERVICE - Erick S Holle (SASI, 2011)
Direct contact in the provision of services provide great opportunities happening maladministration practice (failure to provide service). Therefore, it needs an effort to minimize or even eliminate the practice maladministration by utilizing information and communication technology (ICT) in the frame of electronic-government to service delivery, so that direct contact between service providers and service users no longer occur. In Indonesia, the opportunity for that already exist with the issuance of Presidential Instruction No. 3 of 2003 on National Policy and Strategy Development of electronic-Government (electronic- Government framework), with the aim of supporting the change to democratic governance, facilitating communication between central and local governments, ensure the implementation of the principles of good governance, and facilitating the transformation towards an information society.